Advances in Hemodynamic Analysis in Cardiovascular Diseases Investigation of Energetic Characteristics of Adult and Pediatric Sputnik Left Ventricular Assist Devices during Mock Circulation Support - Alexander A. Pugovkin; Aleksandr G. Markov; Sergey V. Selishchev; Leonie Korn; Marian Walter; Steffen Leonhardt; Leo A. Bockeria; Olga L. Bockeria; Dmitry V. Telyshev (Cardiology Research and Practice)
The need to simulate the operating conditions of the human body is a key factor in every study and engineering process of a bioengineering device developed for implantation. In the present paper, we describe in detail the interaction between the left ventricle (LV) and our Sputnik left ventricular assist devices (LVADs). This research aims to evaluate the influence of different rotary blood pumps (RBPs) on the LV depending on the degree of heart failure (HF), in order to investigate energetic characteristics of the LV-LVAD interaction and to estimate main parameters of left ventricular unloading. We investigate energetic characteristics of adult Sputnik 1 and Sputnik 2 LVADs connected to a hybrid adult mock circulation (HAMC) and also for the Sputnik pediatric rotary blood pump (PRBP) connected to a pediatric mock circulation (PMC). A major improvement of the LV unloading is observed during all simulations for each particular heart failure state when connected to the LVAD, with sequential pump speed increased within 5000–10000 rpm for adult LVADs and 6000–13000 rpm for PRBP with 200 rpm step. Additionally, it was found that depending on the degree of heart failure, LVADs influence the LV in different ways and a significant support level cannot be achieved without the aortic valve closure. Furthermore, this study expands the information on LV-LVAD interaction, which leads to the optimization of the RBP speed rate control in clinics for adult and pediatric patients suffering from heart failure. Finally, we show that the implementation of control algorithms using the modulation of the RBP speed in order to open the aortic valve and unload the LV more efficiently is necessary and will be content of further research.